Teaching controversial issues in a fragile democracy: defusing deliberation in Israeli primary classrooms. Issue 3 (4th May 2018) - Pollak, Itay; Segal, Aliza; Lefstein, Adam; Meshulam, Assaf
Abstract: Teaching through controversial, politically charged issues is promoted in Anglo-American democracies as a key means for cultivating active citizenry and democratic values. However, the challenges of discussing controversial issues in the classroom may differ in younger, deeply divided democracies that lack common ground and institutional stability. In this study we ask, what approaches to the teaching of controversial issues do Israeli teachers adopt while enacting a curricular unit concerning Israel's founding fathers? The data were collected in an ethnographic study in two primary schools during the 2012–2013 school year. We use linguistic ethnographic methods to analyse the curricular materials and their enactment in four video-recorded lessons in three classrooms. We argue that while the curriculum addresses deeply controversial content, it is designed to inculcate a shared national ethos and therefore avoids controversy. In practice, teachers and students engaged with controversial issues, but in ways that defused their volatility. We highlight two heretofore undocumented approaches to controversial issues: (1) sidestepping controversy by stripping it of real world complexities, and (2) scholasticizing the discussion by focusing on literacy practices. Finally, we discuss the rationales for using these two approaches to defuse controversy in the classroom, and their limitations.